Kombinasi Aplikasi Biochar dan Fungi Mikoriza Arbuskula Terhadap Jagung Manis Pada Entisol - Herman, Welly; Zakaria, Edi; Nusantara, Abimanyu Dipo; Gusmara, Herry; Putri, Elsa Lolita (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian Universitas Andalas, 2022)
Entisols are sandy soils with P and K in form still fresh and cannot be absorbed by plants, thereby affecting plant growth and production. Therefore, it is necessary to add rice husk biochar and arbuscular mycorrhizal fungi (AMF) to help provide nutrients to support the growth of sweet corn plants. The research was carried out from August to October 2020 in Beringin Raya Village, Bengkulu City with coordinates S03°45,434' E102°15,687'. The study used a completely randomized design (CRD) with two factors. The first factor was the dose of rice husk biochar: 0, 5, and 10 tons ha-1 ; and the second factor was the AMF dose of 0, 5, and 10 g of propagule. The total 27 units was obtained from nine treatment combinations that was repeated three times. Each experimental unit consisted of 2 sample plants so that there were 54 polybags. Soil parameters observations were soil pH, CEC, organic C, nutrient levels of N, P, K and P uptake. Phosphor uptake was calculated based on the total dry weight of plants x nutrient content of P. The variables observed in plants were plant height, root length, plant dry weight (roots and stems), ear length, cob diameter, cob weight. The result was no interaction between rice husk biochar and AMF on growth, P uptake, and yield of sweet corn. Application 10 tons ha-1 of rice husk biochar of biochar and inoculation of 10 g of plant propagule-1 gave the best results on growth, P uptake, and yield of sweet corn.Keywords: Biochar: Entisols, Mycorrhizal